FAKTOR FAKTOR YANG MEMENGARUHI PRODUKSI USAHATANI JAGUNG PASCA GEMPA DI DESA PANDERE KECAMATAN GUMBASA KABUPATEN SIGI - Jannah, Nur; Tangkesalu, Dance; Alamsyar, Al (Fakultas Pertanian, Universitas Tadulako, 2023)
The aim of this research was to identify the factors that influence corn production after an earthquake in Pandere Village, Gumbasa Sub District, Sigi District. The study was conducted between July and November 2020, with data collected from 35 randomly selected corn farmers. The data was analysed using the Cobb-Douglass production function. The results indicated that the value of F-count (253.962) was greater than the critical F-table value (2.55) at a significance level of α = 5%. This led to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1), indicating that the production factors simultaneously influence corn production significantly whereas partially only the land area had a significant effect on corn production in Pandere Village, Gumbasa District, Sigi Regency. Other factors such as seeds, urea fertilizer, NPK fertilizer, and labor did not show a significant effect on corn production in the same region.